Pengaruh Pemberian Ekstrak Pisang pada Media VW terhadap Induksi Akar dan Pertumbuhan Tunas Dendrobium lasianthera J.J.Sm - EDY SETITI WIDA UTAMI; SUCIPTO HARIYANTO; Y. SRI WULAN MANUHARA (Fakultas Pertanian Universitas Udayana, 2016)
The Effect of Banana Extract at The VW Media on Root Induction and Growth of ShootDendrobium Lasianthera J.J.Sm. Orchid has economic potential as a non-oil exportcommodities which can increase foreign exchange. In addition to supporting industry as cutflowers and potted plants, Dendrobium orchid in particular has been widely recognized as atraditional medicine. Orchids can be propagated in vitro using seed. The main problem in thepropagation of orchid through seed culture is difficulty in root formation. In this study, weevaluated the effect of organic compounds of the banana extract at Vacin and Went mediumcontaining peptone 2 gL-1 to induce growth of root and shoot of the Dendrobium lasianthera.The shoot measuring about 0.3-1.0 cm contain of 1-2 leaves obtained from the seedgermination was cultured on VW medium containing 2 gL-1 peptone additives with 50 gL-1,100 gL-1 and 150 gL-1 banana extract, and without banana extract was used as control. After16 weeks of culture, number of roots, number of leaves, root length, leaf length, the shootheight, root and leaf widest diameters were recorded. Data were statistically analyzed usingANOVA and continued by honestly significance difference (HSD). The results showed thatthe extract of banana statistically gave a significant effect on root induction and growth ofshoot D. lasianthera.